Wireless Real-Time Vehicle Monitoring Based on Android Mobile Device - Čabala, Martin; Gamec, Ján (Acta electrotechnica et informatica, 2012)
The subject of this article is to bring the problem analysis of vehicle communication through diagnostic interface OBDII with diagnostic tools used in automotive diagnostics with an emphasis on Bluetooth communication. Based on the analysis, this paper deals with the description of software design and its implementation to mobile devices on purpose of communication with CAN OBDII interface. For this type of communication is usually used diagnostically-oriented communication processor ELM 327. Aim of this solution is to bring an application provided for mobile devices with Android operating system, which can obtain real time data from engine control unit through ELM 327.